Responsabilidad social empresarial y posicionamiento de la marca del centro comercial La Parada de Iquitos 2024 - Linares Pezo, Victor (2025)
The purpose of this research was to determine how corporate social responsibility affects the positioning of the shopping centre La Parada de Iquitos 2024. Opting for a basic study, descriptive correlational level and non experimental cross-sectional design, the sample consisted of 57 customers for the survey conducted with a questionnaire for data collection. The findings show that corporate social responsibility has a positive influence on the brand positioning of the shopping centre La Parada de Iquitos 2024, as a significance of p=0.000 was obtained. Likewise, the dimensions Brand recall, Brand identification and Brand differentiation have a significance of p=0.000, corporate social responsibility has a positive influence on these dimensions.